A Way to Unlock The Electricity Energy Market for The Common People Using CP Model - Islam, Md. Maidul; Khan, Alimul Haque; Khan, Md. Aman (Engineering International, 2016)
The electricity energy market is almost locked for the people. The trade of electric energy is defined as electricity energy market. In most of the countries, trade of kWh by the people is found very rare practice unlike other businesses. However, business related with energy and power equipment may be accomplished by individual if ones want. On the other hand, selling the kWh is somehow difficult. Few possible reasons that create resistance for a person to enter into electricity energy market such as the large size of power station, higher initial cost and lengthy procedures. This paper discusses the states the power of electricity market and proposes a way to unlock electricity energy market for people using CP (Consumer Producer) model. A way to widen the entry of electricity market may be the minimization of the size of the power station into very small unit which will have lower initial cost, quick as well as easy installation.
Keywords: Consumer-producer uni; Unlock; Electricity market; people; trade of kWh